A safety and feasibility study of cell therapy in dilated cardiomyopathy - Martino,H.F. (2010)
The aim of this study was to determine if bone marrow mononuclear cell (BMMC) transplantation is safe for moderate to severe idiopathic dilated cardiomyopathy (IDC). Clinical trials have shown that this procedure is safe and effective for ischemic patients, but little information is available regarding non-ischemic patients. Twenty-four patients with IDC, optimized therapy, age 46 ± 11.6 years, 17 males, NYHA classes II-IV, and left ventricular ejection fraction <35% were enrolled in the study. Clinical evaluation at baseline and 6 months after stem cell therapy to assess heart function included echocardiogram, magnetic resonance imaging, cardiopulmonary test, Minnesota Quality of Life Questionnaire, and NYHA classification. After cell transplantation 1 patient showed a transient increase in enzyme levels and 2 patients presented arrhythmias that were reversed within 72 h. Four patients died during follow-up, between 6 and 12 weeks after therapy. Clinical evaluation showed improvement in most patients as reflected by statistically significant decreases in Minnesota Quality of Life Questionnaire (63 ± 17.9 baseline vs 28.8 ± 16.75 at 6 months) and in class III-IV NYHA patients (18/24 baseline vs 2/20 at 6 months). Cardiopulmonary exercise tests demonstrated increased peak oxygen consumption (12.2 ± 2.4 at baseline vs 15.8 ± 7.1 mL·kg-1·min-1 at 6 months) and walked distance (377.2 ± 85.4 vs 444.1 ± 77.9 m at 6 months) in the 6-min walk test, which was not accompanied by increased left ventricular ejection fraction. Our findings indicate that BMMC therapy in IDC patients with severe ventricular dysfunction is feasible and that larger, randomized and placebo-controlled trials are warranted.